Customer satisfaction and customer loyalty in Islamic bank: customer engagement as a mediator - Dzulchairi, Mochamad Heru; Saudi, Mohd Haizam Mohd; Yazid, Mohd Faizun Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to investigate the relationship between customer satisfaction towards customer loyalty with the customer engagement as a mediator. This study is to measure the effectiveness of customer engagement as the control variable between customer satisfaction towards customer loyalty. This study is related to customer at the Islamic bank in Indonesia. The study is to measure the factors that lead to customer loyalty as the industry is facing tough competition and relatively new as compared to a commercial and conventional bank. The population if this research is customer who currently owned an account with any of the selected Islamic bank in Indonesia. They must already a customer as the research is to measure between the customer satisfaction towards customer loyalty. 200 respondents were approached to participated in the survey. Questionnaire distributed outside the bank areas upon customer completing their banking activities. All respondent participated on voluntary basis. This research uses e structural equation modeling (SEM) technique together with AMOS. The findings resulted that customer engagement mediated the relationship between customer satisfaction and customer loyalty. Both customer satisfaction and customer engagement have positive relationship towards customer loyalty. It is recommended by Islamic bank I n Indonesia as well as any other bank to implement and exercise more practical customer engagement activities that may raise the strong relationship between customer and bank.